COVID-19 stress and cognitive failures in daily life: A multilevel examination of within- and between-persons patterns - MAJEED, Nadyanna M. (Institutional Knowledge at Singapore Management University, 2023)
The COVID-19 pandemic has claimed an extremely high number of lives worldwide, causing widespread panic and stress. The current research examined whether COVID-19 stress was associated with everyday cognitive failures, using data from a seven-day daily diary study of 253 young adults in Singapore. Multilevel modeling revealed that COVID-19 stress was significantly associated with cognitive failures even after adjusting for demographic factors, both at the within-person and between-persons levels. Specifically, individuals experienced more cognitive failures on days they experienced more COVID-19 stress (as compared to their own average levels of COVID-19 stress), and individuals who experienced more COVID-19 stress overall (as compared to individuals who experienced less COVID-19 stress overall) experienced more cognitive failures in general. While a large body of work has evidenced the detrimental effects of COVID-19 stress on individuals’ well-being, the current findings provide novel insights that these stressors may negatively impact individuals’ cognitive functioning as well.